Happiness Accounting : It's Time to Add Happiness to What We Measure - Pillania, Rajesh K. (Indian Journal of Finance, 2021)
There is a lot of research establishing the need and impact of happiness in the workplace. However, the current accounting system developed a long time ago doesn't include the measurement of happiness. This paper's contribution and uniqueness are that it identified this significant research gap of the lack of inclusion of happiness in the accounting and other measurement systems and established a case for including happiness in the measurement system. The key takeaway is that happiness matters for the corporates as happiness impacts performance, it is about good corporate citizenship, and it is possible to measure happiness. Corporates need to include happiness in the accounting and other performance measurement systems. The implication is to take happiness more seriously as it impacts performance, helps in brand building and reputation, and also is the right thing to do as a good corporate practitioner. More research is needed for creating accounting solutions and systems for including happiness in accounting. Also, there is an urgent need to create a consensus among accounting and measurement professionals on including happiness in the measurement systems. There is a need for lobbying to include happiness in the performance measurement systems and create happiness accounting for firms around the world.